Peran manajemen strategi dalam mewujudkan kualitas unggul pada koperasi syariah - Salsabila, Zakiya (Maliki Interdisciplinary Journal, 2024)
Sharia cooperatives have emerged as an important alternative in economic development in Indonesia, offering a financial system that complies with sharia principles. In the face of increasingly fierce competition and changing member needs, superior quality is a key factor for the sustainability of cooperatives. This research aims to analyze the role of strategic management in improving superior quality in sharia cooperatives, as well as evaluating its impact on member satisfaction. Through a qualitative approach with descriptive methods, data was collected through literature review and analysis of previous research sources. The research results show that strategic management is not only a planning process, but also includes monitoring and adjusting policies that can improve competitiveness and service quality. Sharia cooperatives need to involve all members in decision making and implement innovation in products and services to achieve success and sustainability. Strategic recommendations include improving human resources through training programs, regular market analysis, and technology integration to improve operational efficiency. Thus, the implementation of effective strategic management is expected to create sustainable competitiveness and contribute to the welfare of members and the economic development of society as a whole.